2011
DOI: 10.5032/jae.2011.04098
|View full text |Cite
|
Sign up to set email alerts
|

Considering Professional Identity to Enhance Agriculture Teacher Development

Abstract: The professional identity secondary agriculture teachers display can affect their receptiveness and interest in different professional development events, yet is often overlooked when designing professional development because it is not included in the consensus of proven methods of professional development design and delivery (Desimone, 2009). Currently, there is a gap in determining the effects of addressing the professional identity of agriculture teachers in professional development. We posit that, due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Others have indicated, "In-service and professional development activities are often the primary methods used to improve teacher quality" (Christensen, et al, 2009, p. 2). Professional development opportunities enhance multiple skills for teachers, and those enhanced skills are used to improve student learning (Shoulders & Myers, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have indicated, "In-service and professional development activities are often the primary methods used to improve teacher quality" (Christensen, et al, 2009, p. 2). Professional development opportunities enhance multiple skills for teachers, and those enhanced skills are used to improve student learning (Shoulders & Myers, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Assessing teachers prior to attending a professional development event can better serve the teachers (Rice & Kitchel, 2015). Teachers are expected to attend professional development events to improve their skills and increase student learning (Shoulders & Myers, 2011). When preservice students are student teaching, pre-service professional development events should be considered to help prevent barriers pre-service students might face.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the problems and challenges instructors of online courses encounter (McConnell, 2000) as well as students' low performance on the test of general global knowledge, officials in CASNR should provide instructors professional development in the use of effective instructional strategies and teaching methods. Agricultural education, teacher education, faculty members, whose departments are often located in colleges of agriculture, are uniquely qualified to provide this kind of professional development for their colleagues (Shoulders & Myers, 2011;Westfall-Rudd, 2011). CASNR officials should also provide regular workshops, symposia, and seminars intended to keep instructors informed of the latest developments in the field of agriculture that resonate with global issues and how best to instruct such to students irrespective of a course's mode of delivery.…”
Section: Recommendations For Practicementioning
confidence: 99%
“…Terry and Briers (2010) encouraged agriculture teachers to build relationships with colleagues in their schools and with peers in the agricultural education profession both state-and nation-wide. However, Shoulders and Myers (2011) suggested that agriculture teachers have a unique professional identify which differs from the professional identity of educators in other subject areas, which may cause challenges in the formation of effective critical friendships between agriculture teachers and colleagues within their schools. An examination into how preservice agriculture teachers are able to establish and use critical friendships within and outside of the discipline can assist the profession in utilizing critical friendships in ways that improve self and peer reflection, and in turn, teaching behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…3. Agricultural education has historically been a male-dominated profession (Camp, Broyles, & Skelton, 2002;Kelsey, 2006), while most other teaching disciplines have historically been female-dominated (Paechter & Head, 1996;Shoulders & Myers, 2011;Skelton, 2003). 4.…”
Section: Introductionmentioning
confidence: 99%